2021
DOI: 10.3390/antiox10010053
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chemical Composition, Radical Scavenging and Antitumor Activities of Satureja hortensis L. Herb Extracts

Abstract: Satureja hortensis L. is an annual herbaceous plant of the Lamiaceae Lindl. family. S. hortensis L., related to thyme and rosemary, is used as spice and traditional medicinal herb in Europe. Mainly due to the polyphenols contained in S. hortensis L., this plant exhibits multiple biological effects. However, therapeutic effects on cells, including skin tumors, have not yet been studied. Therefore, the aim of this study was to compare the composition and the resulting antioxidant as well as biological properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…глисної активності ефірних олій чаберів науковці пояснюють домінуванням тимолу, карвакролу та інших ароматичних сполук [9][10][11][12]. Науковці [13,14] припускають, що значний антиоксидантний потенціал екстрактів S. hortensis і S. montana наводить на думку про можливість їхнього застосування у лікуванні онкологічних захворювань. Оскільки ці два види роду Satureja придатні до культивування в умовах помірного клімату, відкривається перспектива отримання достатнього обʼєму сировини для їхнього комплексного фармакогностичного аналізу та подальшого засто сування у фармації [15].…”
Section: Phytochemical Researchesunclassified
See 2 more Smart Citations
“…глисної активності ефірних олій чаберів науковці пояснюють домінуванням тимолу, карвакролу та інших ароматичних сполук [9][10][11][12]. Науковці [13,14] припускають, що значний антиоксидантний потенціал екстрактів S. hortensis і S. montana наводить на думку про можливість їхнього застосування у лікуванні онкологічних захворювань. Оскільки ці два види роду Satureja придатні до культивування в умовах помірного клімату, відкривається перспектива отримання достатнього обʼєму сировини для їхнього комплексного фармакогностичного аналізу та подальшого засто сування у фармації [15].…”
Section: Phytochemical Researchesunclassified
“…Цю сполуку розглядають як біологічно активний поліфенол із доведеними протизапальними антиоксидантними, антимікробними, антидіабетичними, гепатопротекторними, нейропротекторними та іншими лікувальними властивостями [23]. Домінування цієї гідроксикоричної кислоти у сировині представників роду Satureja було відзначено багатьма іншими дослідниками [5,6,13,19,24,25]. Так, сербські науковці Boroja та співавт.…”
Section: таблицяunclassified
See 1 more Smart Citation
“…The major biomolecules found in extracts and essential oils of S. hortensis are volatile oils, phenolic compounds, flavonoids, tannins, steroids, acids, gums, mucilage, and pyrocatechols. The main components isolated from essential oils are carvacrol, thymol, cymene, terpinene, while alcoholic extracts are dominated by rosmarinic acid, caffeic acid, naringenin, isoferulic acid, luteolin, quercetin, and apigenin [33][34][35][36]. These bioactive compounds have been found to have a variety of biological activities including antioxidant, antispasmodic, anti-inflammatory, analgesic, antidiabetic, hepatoprotective, immunostimulant, reproduction stimulatory, vasodilatory, antimicrobial, and antiparasitic [32,34,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Pinus pinaster bark extracts also showed an anticancer effect by decreasing cell viability in human lung cancer cells [14]. Studies realized with Satureja hortensis L. herb have shown that the budding phase alcohol extracts of this plant contain the largest amounts of polyphenols, including rutin and rosemary acid, which promote the radical scavenging activity and antioxidant properties with an anticancer effect on tumor skin cells [22]. In this way, Phoenix dactylifera seed extract can also be used as a skin whitening agent by attenuating melanogenesis in B16F10 cells by downregulating protein kinase A (PKA) signaling pathways [23].…”
mentioning
confidence: 99%